How do public health professionals view and engage with research? A qualitative interview study and stakeholder workshop engaging public health professionals and researchers - Peter van der Graaf; Lynne F. Forrest; Jean Adams; Janet Shucksmith; Martin White (BMC, 2017)
Abstract Background With increasing financial pressures on public health in England, the need for evidence of high relevance to policy is now stronger than ever. However, the ways in which public health professionals (PHPs) and researchers relate to one another are not necessarily conducive to effective knowledge translation. This study explores the perspectives of PHPs and researchers when interacting, with a view to identifying barriers to and opportunities for developing practice that is effectively informed by research. Methods This research focused on examples from two responsive research schemes, which provide university-based support for research-related enquiries from PHPs: the NIHR SPHR Public Health Practitioner Evaluation Scheme1 and the responsive research service AskFuse2. We examined enquiries that were submitted to both between 2013 and 2015, and purposively selected eight enquiries for further investigation by interviewing the PHPs and researchers involved in these requests. We also identified individuals who were eligible to make requests to the schemes but chose not to do so. In-depth interviews were conducted with six people in relation to the PHPES scheme, and 12 in relation to AskFuse. The interviews were transcribed and analysed using thematic framework analysis. Verification and extension of the findings were sought in a stakeholder workshop. Results PHPs recognised the importance of research findings for informing their practice. However, they identified three main barriers when trying to engage with researchers: 1) differences in timescales; 2) limited budgets; and 3) difficulties in identifying appropriate researchers. The two responsive schemes addressed some of these barriers, particularly finding the right researchers to work with and securing funding for local evaluations. The schemes also supported the development of new types of evidence. However, other barriers remained, such as differences in timescales and the resources needed to scale-up research. Conclusions An increased mutual awareness of the structures and challenges under which PHPs and researchers work is required. Opportunities for frequent and meaningful engagement between PHPs and researchers can help to overcome additional barriers to co-production of evidence. Collaborative models, such as the use of researchers embedded in practice might facilitate this; however, flexible research funding schemes are needed to support these models.